Molecular detection and antibiogram of Staphylococcus aureus in rabbits, rabbit handlers, and rabbitry in Terengganu, Malaysia - Chai, Min Hian; Sukiman, Muhammad Zikree; Najib, Nurlailasari Mohammad; Mohabbar, Nor Arifah; Azizan, Nur Aina Nadhirah Mohd; Mohamad, Noor Muzamil; Ariffin, Siti Mariam Zainal; Ghazali, Mohd Faizal (Journal of Advanced Veterinary and Animal Research, 2021)
Objectives: This study aims to investigate the prevalence and antibiogram of Staphylococcus aureus and methicillin-resistance S. aureus (MRSA) in rabbits, rabbit handlers, and rabbitry environments in Terengganu. Materials and Methods: Swab samples from 183 rabbits (183 oral and 183 ear swabs), 45 rabbit handlers (45 oral and 45 nasal), and environmental (n = 180) samples from rabbitries were collected from 10 rabbit farms in Terengganu. The associated S. aureus isolates from the swabs were isolated using phenotypic microbiology tests. The bacteria were confirmed by polymerase chain reaction targeting nuc (S. aureus) and mecA (MRSA) genes. The antibiogram of all S. aureus isolates was determined using the Kirby–Bauer test. Results: Staphylococcus aureus was detected in 19% of rabbits, 26.7% of rabbit handlers, and 8.8% of swabs from the rabbitry environment. However, MRSA (0%) could not be detected. Antibiotic susceptibility test revealed that S. aureus from rabbits showed low resistance (<20%) against 15 different antibiotics while fully susceptible to 4 antibiotics. Meanwhile, S. aureus from rabbit handlers showed high resistance against penicillin (86%), oxacillin (64%), and amoxicillin (50%). Conclusions: This study suggests the emergence of antibiotic-resistant S. aureus in rabbit farms settings. Therefore, careful selection of antimicrobial agents will be essential to preserve the effectiveness of treatments toward S. aureus infections. J. Adv. Vet. Anim. Res., 8(3): 388-395, September 2021 http://doi.org/10.5455/javar.2021.h527